Trace analysis of environmental matrices by large-volume injection and liquid chromatography-mass spectrometry - Busetti, Francesco; Backe, W.; Bendixen, N.; Maier, U.; Place, B.; Giger, W.; Field, J. (Springer, 2011)
The time-honored convention of concentrating aqueous samples by solid-phase extraction (SPE) is being challenged by the increasingly widespread use of large-volume injection (LVI) liquid chromatography–mass spectrometry (LC–MS) for the determination of traces of polar organic contaminants in environmental samples. Although different LVI approaches have been proposed over the last 40 years, the simplest and most popular way of performing LVI is known as single-column LVI (SC-LVI), in which a large-volume of an aqueous sample is directly injected into an analytical column. For the purposes of this critical review, LVI is defined as an injected sample volume that is ≥10% of the void volume of the analytical column. Compared with other techniques, SC-LVI is easier to set up, because it requires only small hardware modifications to existing autosamplers and, thus, it will be the main focus of this review. Although not new, SC-LVI is gaining acceptance and the approach is emerging as a technique that will render SPE nearly obsolete for many environmental applications.In this review, we discuss: the history and development of various forms of LVI; the critical factors that must be considered when creating and optimizing SC-LVI methods; and typical applications that demonstrate the range of environmental matrices to which LVI is applicable, for example drinking water, groundwater, and surface water including seawater and wastewater. Furthermore, we indicate direction and areas that must be addressed to fully delineate the limits of SC-LVI.